Reforma estatal, accountability e metas do Judiciário: as influências de uma administração baseada na busca por resultados no elemento qualitativo da prestação jurisdicional. - Ferreira, Pedro Henrique Azevedo Lopes (2019)
The Public Administration has experienced significant changes over the last years focused primarily on the insertion of market mechanisms at the state level in order to make it more efficient. The Judiciary did not remain inert to this movement, being guided by an impetus to ensure speed of judgment and increase its productivity. Given this framework, this study intends to analyze whether the application of market efficiency criteria inthe judicial administration was able to generate, in addition to the intended increase in productivity, an improvement in the quality of the judicial service, or, on the other hand, if such aspect was left out of the equation. In the first chapter, Constitutional Amendments 19 and 45, which reformed the Public Administration in general and in the Judiciary, were analyzed, telling their historical and relevant aspects. In addition, the phenomenon of accountability was studied, in order to highlight the obligation of public agents to account. In the second chapter, it was studied how accountability is given in the scope of the National Council of Justice and the Court of Justice of Ceará, in order to clarify if what is being demanded of the judiciary is only an increase of productivity or, also an improvement in the quality of the judicial service. Once a qualitative deficit of accountability was evidenced, the second chapter sought to rework the concepts of the principles of efficiency and the reasonable duration of process, commonly invoked by the judicial administration to justify its performance focused on productivity. Finally, in the third chapter, the duty / guarantee of reasoning of judicial decisions and the Toulmin model of rational argumentation were presented as important parts in the equilibrium of the balance of the binomial quality / quantity, so that, in the end, solutions to the specific problems evidenced throughout the study, all with the purpose of recovering the qualitative factor of the jurisdictional service.